The Didcot Demolition - Alford, Roland (International Society of Explosives Engineers, 2025)
In the modern world of demolition safety is paramount and unnecessary or unquantifiable risks are not accepted (FasterCapital, 2024) and all risks must be kept As Low As Reasonably Practicable (ALARP) (BSI, 2017). This principle has led to a huge reduction in deaths in the last 50 years and the statistics continue to improve although this is starting to plateau (Beal, 2007). Under normal circumstances, this is now simply part of the normal way work is done and systems are in place to ensure both safety and economic profits are assured. What happens when the environment is less controlled and risks are unknown, such as after a natural disaster, war, an accident or a stand-up from a failed demolition attempt? A dangerous structure cannot responsibly be left alone with a fence around it so some action must be taken, but how can this be done safely and responsibly? An incident in Didcot, England in which half of a power station’s boiler house being prepared for an explosive demolition collapsed suddenly, killing four men in 2016 provides a useful case study of how technology, creativity and planning can be used to conduct complex demolition fully remotely to avoid any further risk to life.